Kesiapan Perusahaan dalam Penerapan Balance Scorecard: Studi Kasus Pada PT A - Lianto, Catherine Nathaniela; Andono, Fidelis Arastyo (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2022)
This study aims to explore important aspects that determine the company's readiness to implement the Balanced Scorecard (BSC) system. Using qualitative methods, this research was conducted by studying the case of PT A which is engaged in the manufacturing industry. The data collected were analyzed with an interpretive approach. The results of this study indicate that there are some discrepancies in the characteristics of the company and the BSC that require further adjustment. There were 8 problems found, namely: (1) lack of understanding of the BSC, (2) the absence of an adequate information system, (3) the absence of overall support, (4) lagging indicators and leading indicators that have not been integrated, (5) inadequate performance measurement indicators, (6) Some indicators do not have clear targets, (7) incompetent workforce, and (8) common measurement bias. The implementation of an integrated measurement system based on the BSC cannot be done without prior evaluation of the characteristics and readiness of the organization in implementing the BSC. As qualitative research, the results of this study cannot be generalized to a wider research context. However, this research is expected to contribute to the management accounting literature in the context of preparing for the implementation of BSC in manufacturing companies.